About Innovative Methods of Teaching Natural Sciences in Elementary Grades - qizi , Hakimova Shahzoda Hamidjon (Research Parks Publishers, 2023)
In this article, the methods of organizing elementary science lessons based on innovative technologies are scientifically and theoretically analyzed.